Composite modifier, modified neodymium-iron-boron magnetic powder, sintered neodymium-iron-boron magnet, method and application

By using the composite modified agent to modify the iron boron magnetic powder, the problem that it is difficult to improve the fluidity and magnetic performance of the traditional modified agent that is difficult to improve the traditional modifiers, and realize the high magnetic performance and density of the sintering cymbal iron boron magnet, which reduces the impurities.

CN119340054APending Publication Date: 2025-01-21BAOTOU RESEARCH INSTITUTE OF RARE EARTHS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411493775.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Traditional liquid organic modifiers are difficult to meet the needs of anti-oxidation treatment and fluid improvement of ultrafine magnetic powder and high-abundance magnetic powder, resulting in insufficient magnetic properties of sintered NdFeB magnets, and have poor coating effect, easy volatility, heavy odor, etc. Disadvantages, cannot meet the requirements of high temperature forming and density.

Method used

The composite modifiers composed of the first modifier and the second modified agent are used to modify the iron boron magnetic powder. The first modifier includes the first organic molybdenum compound, the solid organic matter, and the solid -state inorganic object. The second modifier includes the second organic molybdenum compound and liquid organic matter.

Benefits of technology

It significantly improves the magnetic properties of sintering rigid iron boron magnets, including the improvement of the remaining magnetic, stubborn power and maximum magnetic energy accumulation. At the same time, the content of carbon and oxygen is reduced, the density and molding performance of the blank are omitted, and the static pressure process is omitted. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340054A_ABST
    Figure CN119340054A_ABST
Patent Text Reader

Abstract

The invention discloses a composite modifier, modified neodymium-iron-boron magnetic powder, a sintered neodymium-iron-boron magnet, a method and application. A composite modifier for neodymium iron boron magnetic powder is formed by a first modifier and a second modifier, the first modifier comprises a first organic molybdenum compound, a solid organic matter and a solid inorganic matter; the second modifier comprises a second organic molybdenum compound and a liquid organic matter. The composite modifier can be used for modifying neodymium-iron-boron magnetic powder, and the magnetic performance of the prepared sintered neodymium-iron-boron magnet can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of permanent magnetic materials, and in particular relates to a composite modifier, modified NdFeB magnetic powder, a sintered NdFeB magnet, a method and an application thereof. Background Art

[0002] As a permanent magnet material, sintered NdFeB magnets have become the core material in cutting-edge technology fields such as new energy vehicle drive motors and robot servo systems in today's rapidly developing technological era. Their importance is self-evident. Sintered NdFeB magnets provide powerful power support for modern industrial equipment with their excellent magnetic properties. With the booming new energy vehicle industry and the increasing maturity of robot technology, the demand for high-end sintered NdFeB magnets is showing an explosive growth trend.

[0003] The production process of sintered NdFeB magnets is inseparable from the preparation of magnetic powder. The performance of NdFeB magnetic powder directly determines the performance of the final magnet. The quality and processing technology of magnetic powder largely determine its performance. However, traditional liquid organic modifiers have been difficult to meet the needs of anti-oxidation treatment and fluidity improvement of ultrafine magnetic powder and high-abundance magnetic powder, which is not conducive to improving the magnetic properties of the resulting sintered NdFeB magnets. In addition, traditional liquid organic modifiers have the disadvantages of poor coating effect, easy volatility, and strong odor. In addition, their pressing molding performance and green compact density are not good, and they cannot meet the green compact one-time molding index requirements. The residual carbon formed by high-temperature carbonization interacts with the neodymium-rich phase at the grain boundary, which may also deteriorate the magnet performance.

[0004] CN115896643A discloses a molybdenum nanopowder composite NdFeB magnet and its preparation method, which is made of a main alloy and an auxiliary alloy. After the main alloy and the auxiliary alloy are evenly mixed, a molded body is obtained by a magnetic field molding method or hot pressing deformation, and then sintered at 1020-1070°C for 5 hours in a vacuum or inert gas, and then subjected to aging treatment to obtain a composite NdFeB magnet. The method uses molybdenum nanopowder, which is beneficial to reducing the oxygen content of the magnet, but the maximum magnetic energy product and other properties are not significantly improved.

[0005] CN115331941A discloses a method for modifying high-fluidity sintered NdFeB magnetic powder, which mainly includes: injecting the sintered NdFeB magnetic powder and the modifier after airflow milling into a mixing container in a specific manner under the protection of an inert atmosphere, and mixing the powder and the modifier by a mixing method of impact, shearing and rotation. In this method, the liquid modifier is one or more of dimethylformamide, methyl octanoate, n-octane, methyl octanoate, acetone, petroleum ether, aviation gasoline, silicone oil, and ethylene glycol; the solid modifier is one or more of aluminate coupling agent, polyamide wax powder, ethylene bis stearamide, benzoic acid, zinc stearate, paraffin, ZrO2, nano Al2O3 powder, nano Cu powder, and nano Al powder. The maximum magnetic energy product performance of the sintered NdFeB magnet obtained in this method has not been improved, and the oxygen content of the magnet has not been improved.

[0006] CN117936258A discloses a process for preparing high-performance NdFeB magnets by hot pressing, including: preparation of doped alloy powder, preparation of NdFeB magnetic powder, modification of NdFeB magnetic powder, pretreatment of hot pressing mold and hot deformation mold, and preparation of NdFeB magnets by hot pressing. The process uses a liquid modifier of an anhydrous ethanol solution of triaminopropyltriethoxysilane and polyvinylpyrrolidone to modify the NdFeB magnetic powder, which only improves the dispersibility of the magnetic powder and has little effect on improving the magnetic properties of the NdFeB magnet. Summary of the invention

[0007] One object of the present invention is to provide a composite modifier for NdFeB magnetic powder, which can be used for the modification of NdFeB magnetic powder, thereby facilitating the improvement of the magnetic properties of the obtained sintered NdFeB magnet. Another object of the present invention is to provide a method for preparing modified NdFeB magnetic powder using the composite modifier as described above. Another object of the present invention is to provide a modified NdFeB magnetic powder. Another object of the present invention is to provide a method for preparing a sintered NdFeB magnet and a sintered NdFeB magnet. Another object of the present invention is to provide an application of the composite modifier as described above in improving the magnetic properties of a sintered NdFeB magnet.

[0008] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.

[0009] In one aspect, the present invention provides a composite modifier for NdFeB magnetic powder, which is formed by a first modifier and a second modifier.

[0010] Wherein, the first modifier comprises a first organic molybdenum compound, a solid organic substance and a solid inorganic substance; the second modifier comprises a second organic molybdenum compound and a liquid organic substance;

[0011] Wherein, the solid organic matter is selected from at least one of higher alcohols, higher carboxylic acids, higher fatty acid esters and amide compounds; the solid inorganic matter is a two-dimensional layered substance selected from at least one of molybdenum disulfide, tungsten disulfide and vanadium selenide; the liquid organic matter includes fatty acid esters and organic boron compounds;

[0012] wherein the first organic molybdenum compound is the same as or different from the second organic molybdenum compound;

[0013] Wherein, based on the total weight of the first modifier, the weight percentage of the first organic molybdenum compound is 0.3-15wt%, and the weight percentage of the solid inorganic substance is 0.02-4.8wt%;

[0014] Wherein, based on the total weight of the second modifier, the weight percentage of the second organic molybdenum compound is 0.2 to 18 wt %;

[0015] Wherein, the weight ratio of the first modifier to the second modifier is 0.4-0.95:0.3-0.8.

[0016] According to the composite modifier of the present invention, preferably, the first organic molybdenum compound or the second organic molybdenum compound is selected from one or more of a molybdenum amine complex, molybdenum cyclopentaneate, nitrogen-containing dialkyl dithiophosphate oxymolybdenum, dialkyl dithiocarbamate molybdenum, dialkyl dithiophosphate oxymolybdenum, alkyl salicylate molybdenum and isooctanoic acid molybdenum.

[0017] According to the composite modifier of the present invention, preferably, the higher alcohol is selected from at least one of tetradecanol, hexadecanol, stearyl alcohol and eicosyl alcohol; the higher carboxylic acid is selected from at least one of lauric acid, myristic acid, palmitic acid and stearic acid; the higher fatty acid ester is selected from at least one of lauric acid monoglyceride, myristic acid glyceride and palmitic acid glyceride; the amide compound is selected from at least one of oleamide, ethylene bisoleamide, palmitic acid amide, oleyl palmitic acid amide, stearic acid amide, ethylene biserucic acid amide and erucic acid amide;

[0018] The fatty acid ester is selected from at least one of isooctyl oleate, methyl oleate, methyl palmitate, methyl stearate and methyl laurate; the organic boron compound is selected from at least one of triethanolamine borate, triisopropyl borate, tributyl borate and triethyl borate.

[0019] On the other hand, the present invention also provides a method for preparing modified NdFeB magnetic powder using the composite modifier as described above, comprising the following steps:

[0020] 1) smelting and crushing raw materials including rare earth alloy to obtain rare earth alloy coarse powder;

[0021] 2) adding a first modifier to the rare earth alloy coarse powder, and continuing to refine and crush to obtain rare earth alloy fine powder; wherein the weight percentage of the first modifier to the rare earth alloy coarse powder is 0.4-0.95‰;

[0022] 3) adding a second modifier to the rare earth alloy fine powder and mixing them to obtain modified NdFeB magnetic powder, wherein the weight percentage of the second modifier to the rare earth alloy fine powder is 0.3-0.8‰.

[0023] According to the method of the present invention, preferably,

[0024] The particle size of the rare earth alloy coarse powder ranges from 68 to 368 μm;

[0025] The rare earth alloy fine powder has a D 90 / D 10 The average specific surface area diameter is 3.7-4.46, the average specific surface area diameter is 2.45-2.68 μm, the repose angle is 43.5°-43.8°, and the bulk density is 1.72-1.76 g / cm 3 , tap density greater than or equal to 3.76g / cm 3 .

[0026] In another aspect, the present invention further provides a modified NdFeB magnetic powder, which is prepared according to the method described above.

[0027] In another aspect, the present invention further provides a method for preparing a sintered NdFeB magnet, the method comprising the following steps:

[0028] The modified NdFeB magnetic powder is pressed and sintered to obtain a sintered NdFeB magnet.

[0029] According to the preparation method of the present invention, preferably, the sintering process comprises:

[0030] Vacuum heat treatment: Place the pressed green body into a sintering furnace. -1 Pa, start heating to the first temperature zone of 180-460°C, and keep it in the first temperature zone for 30-120 minutes, then heat up to the second temperature zone of 320-480°C, and keep it in the second temperature zone for 30-120 minutes, then heat up to the third temperature zone of 1030-1105°C, and keep it at this temperature for 2-6 hours;

[0031] Aging treatment: For the first stage of aging, the temperature is raised to 870-950℃ and kept at this temperature for 0.5-5h; for the second stage of aging, the temperature is kept at 400-665℃ for 1-5h; after the aging treatment, it is cooled to room temperature.

[0032] In another aspect, the present invention further provides a sintered NdFeB magnet, which is prepared according to the preparation method as described above.

[0033] Finally, the present invention also provides an application of the composite modifier as described above in improving the magnetic properties of a sintered NdFeB magnet, wherein the remanence of the sintered NdFeB magnet is increased by greater than or equal to 0.1 kGs, the coercive force is increased by greater than or equal to 1 kOe, the maximum magnetic energy product is increased by greater than or equal to 0.9 MGOe, and the squareness is increased by greater than or equal to 0.6%.

[0034] The composite modifier of the present invention can be used for the modification of NdFeB magnetic powder. By using the first modifier and the second modifier in coordination, the fluidity and dispersibility of the NdFeB magnetic powder can be better improved, which is conducive to molding and orientation. The orientation is stable, which is conducive to obtaining a compact with a higher density, and the cumbersome process of isostatic pressing can be omitted. Furthermore, the addition amount of the composite modifier of the present invention is small. In addition, the magnetic properties of the sintered NdFeB magnet obtained by using the modified NdFeB magnetic powder containing the composite modifier of the present invention are significantly improved, and the carbon content and oxygen content are significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a process flow chart for preparing sintered NdFeB magnets. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0037] <Compound modifier for NdFeB magnetic powder>

[0038] The composite modifier for NdFeB magnetic powder provided by the present invention is formed by a first modifier and a second modifier, wherein the first modifier includes a first organic molybdenum compound, a solid organic matter and a solid inorganic matter; the second modifier includes a second organic molybdenum compound and a liquid organic matter. The weight ratio of the first modifier to the second modifier is 0.4-0.95:0.3-0.8, preferably 0.5-0.8:0.4-0.7, and more preferably 0.5-0.7:0.4-0.6. Such a composite modifier is conducive to improving the fluidity and oxidation resistance of the obtained NdFeB magnetic powder, and the orientation is stable, and the green compact can be formed in one time, and the pressing forming performance and green compact density can be improved. The obtained NdFeB magnetic powder is conducive to improving the magnetic properties of the obtained sintered NdFeB magnet, and the carbon and oxygen content therein is low.

[0039] When the present invention is used to form NdFeB magnetic powder, the total addition amount of the composite modifier of the present invention is 0.7-1.75wt‰ of the mass of the NdFeB magnetic powder, preferably 0.7-1.2wt‰, and more preferably 0.75-0.95wt‰.

[0040] The first modifier

[0041] In certain embodiments, the first modifier consists only of a first organomolybdenum compound, a solid organic substance, and a solid inorganic substance.

[0042] The first organic molybdenum compound is selected from one or more of a molybdenum amine complex, molybdenum cyclopentane acid, nitrogen-containing dialkyl dithiophosphoryl molybdenum, dialkyl dithiocarbamate molybdenum, dialkyl dithiophosphoryl molybdenum, alkyl salicylic acid molybdenum and isooctanoic acid molybdenum. Preferably, the first organic molybdenum compound is selected from one of dialkyl dithiocarbamate molybdenum and cyclopentane acid molybdenum.

[0043] The solid organic matter is selected from at least one of higher alcohols, higher carboxylic acids, higher fatty acid esters and amide compounds. Preferably, the solid organic matter is selected from at least one of higher alcohols, higher carboxylic acids, higher fatty acid esters and amide compounds.

[0044] The higher alcohol is selected from at least one of tetradecanol, hexadecanol, stearyl alcohol and eicosanol. Preferably, the higher alcohol is selected from one of tetradecanol, hexadecanol, stearyl alcohol and eicosanol.

[0045] The higher carboxylic acid is selected from at least one of lauric acid, myristic acid, palmitic acid and stearic acid. Preferably, the higher carboxylic acid is selected from one of lauric acid, myristic acid, palmitic acid and stearic acid.

[0046] The higher fatty acid ester is selected from at least one of lauric acid monoglyceride, myristic acid glyceride and palmitic acid glyceride. Preferably, the higher fatty acid ester is selected from one of lauric acid monoglyceride, myristic acid glyceride and palmitic acid glyceride.

[0047] The amide compound is selected from at least one of oleamide, ethylenebisoleamide, oleylpalmitamide, stearamide (also known as octadecylamide), palmitic acid amide, ethylenebiserucamide and erucamide.

[0048] According to one embodiment of the present invention, the solid organic matter is an amide compound.

[0049] According to a specific embodiment of the present invention, the solid organic matter is a mixture of stearic acid amide, oleic acid amide and ethylenebiserucic acid amide, wherein the sum of the masses of stearic acid amide and oleic acid amide accounts for greater than or equal to 76wt%, and the mass ratio of stearic acid amide to oleic acid amide is 20:80 to 50:50.

[0050] According to another specific embodiment of the present invention, the solid organic matter is a mixture of palmitic acid amide, erucic acid amide and ethylene bisoleamide, wherein the sum of the masses of palmitic acid amide and erucic acid amide accounts for no less than 82 wt%, and the mass ratio of palmitic acid amide to erucic acid amide is 35:65 to 40:60.

[0051] The solid inorganic substance is a two-dimensional layered substance, and is selected from at least one of molybdenum disulfide, tungsten disulfide and vanadium selenide. Preferably, the solid inorganic substance is selected from one of molybdenum disulfide and tungsten disulfide.

[0052] Based on the total weight of the first modifier, the weight percentage of the first organic molybdenum compound is 0.3-15wt%, preferably 0.5-11.3wt%, more preferably 0.6-9.3wt%, more preferably 1.0-7.3wt%, and more preferably 2.5-7.3wt%. Based on the total weight of the first modifier, the weight percentage of the solid inorganic substance is 0.02-4.8wt%, preferably 0.1-4.5wt%, more preferably 0.5-4.0wt%, and more preferably 1.0-3.5wt%.

[0053] In certain embodiments, the preparation of the first modifier comprises the following steps: adding a first organic molybdenum compound to a solid organic matter, crushing it under inert gas protection to form a uniformly mixed powder, and then adding a solid inorganic matter to the uniformly mixed powder, mixing them uniformly, to obtain the first modifier.

[0054] The inert gas may be argon, helium or nitrogen. The first modifier may be spherical particles.

[0055] According to a specific embodiment of the present invention, the first modifier is formed by a first organic molybdenum compound, a solid organic matter and a solid inorganic matter, wherein the first organic molybdenum compound is dialkyl dithiocarbamate molybdenum, the solid organic matter is a mixture of palmitic acid amide, erucic acid amide and ethylene bisoleic acid amide, the sum of the masses of palmitic acid amide and erucic acid amide accounts for more than 82wt% of the total mass of the solid organic matter, and the solid inorganic matter is nano molybdenum disulfide; based on the total weight of the first modifier, the weight percentage of the first organic molybdenum compound is 7-7.3wt%; the weight percentage of the solid inorganic matter is 1-1.4wt%.

[0056] According to another specific embodiment of the present invention, the first modifier is formed by a first organic molybdenum compound, a solid organic matter and a solid inorganic matter, wherein the first organic molybdenum compound is oily molybdenum cyclopentaneate, the solid organic matter is a mixture of stearic acid amide, oleic acid amide and ethylenebiserucic acid amide, wherein the sum of the masses of stearic acid amide and oleic acid amide accounts for more than 76wt% of the total mass of the solid organic matter, and the solid inorganic matter is nano tungsten disulfide; based on the total weight of the first modifier, the weight percentage of the first organic molybdenum compound is 2.5-3.8wt%; the weight percentage of the solid inorganic matter is 2-3.5wt%.

[0057] Second Modifier

[0058] In certain embodiments, the second modifier consists only of a second organomolybdenum compound and a liquid organic material.

[0059] The second organic molybdenum compound is selected from one or more of a molybdenum amine complex, molybdenum cyclohexane acid, nitrogen-containing dialkyl dithiophosphoric acid oxymolybdenum, dialkyl dithiocarbamate molybdenum, dialkyl dithiophosphoric acid oxymolybdenum, alkyl salicylic acid molybdenum and isooctanoic acid molybdenum. Preferably, the second organic molybdenum compound is selected from one of a molybdenum amine complex, molybdenum cyclohexane acid, nitrogen-containing dialkyl dithiophosphoric acid oxymolybdenum, dialkyl dithiocarbamate molybdenum, dialkyl dithiophosphoric acid oxymolybdenum, alkyl salicylic acid molybdenum and isooctanoic acid molybdenum.

[0060] The first organomolybdenum compound is the same as or different from the second organomolybdenum compound. In certain embodiments, the first organomolybdenum compound and the second organomolybdenum compound are the same. In other embodiments, the first organomolybdenum compound and the second organomolybdenum compound are different.

[0061] The liquid organic matter includes fatty acid esters and organoboron compounds. In certain embodiments, the liquid organic matter consists only of fatty acid esters and organoboron compounds.

[0062] The fatty acid ester is selected from saturated fatty acid ester or unsaturated fatty acid ester, such as at least one of isooctyl oleate, methyl oleate, methyl palmitate, methyl stearate and methyl laurate, preferably selected from one of isooctyl oleate, methyl palmitate, methyl stearate and methyl laurate, more preferably selected from isooctyl oleate.

[0063] The organic boron compound is selected from at least one of triethanolamine borate, triisopropyl borate, tributyl borate and triethyl borate, preferably selected from one of triethanolamine borate, triisopropyl borate, tributyl borate and triethyl borate, more preferably selected from triethanolamine borate or triethyl borate.

[0064] Based on the total weight of the second modifier, the weight percentage of the second organic molybdenum compound is 0.2 to 18 wt %, preferably 0.3 to 12 wt %, further preferably 0.42 to 7.5 wt %, and more preferably 0.45 to 2.5 wt %.

[0065] In certain embodiments, the preparation of the second modifier comprises the following steps: mixing a fatty acid ester and an organic boron compound in proportion to obtain a liquid organic matter, and then adding a second organic molybdenum compound to the liquid organic matter and mixing to obtain the second modifier.

[0066] The second modifier is a solution or a suspension.

[0067] According to a specific embodiment of the present invention, the second modifier is composed of a second organic molybdenum compound and a liquid organic matter, wherein the second organic molybdenum compound is a molybdenum amine complex, and the liquid organic matter is obtained by mixing isooctyl oleate and triethanolamine borate in a volume ratio of 2 to 3:1; based on the total weight of the second modifier, the molybdenum amine complex accounts for 0.45 to 0.55 wt%.

[0068] According to another specific embodiment of the present invention, the second modifier is composed of a second organic molybdenum compound and a liquid organic matter, wherein the second organic molybdenum compound is alkyl salicylate molybdenum, and the liquid organic matter is obtained by mixing isooctyl oleate and triethyl borate in a volume ratio of 4 to 5:3; based on the total weight of the second modifier, the proportion of alkyl salicylate molybdenum is 1.2 to 1.58 wt%.

[0069] According to another specific embodiment of the present invention, the second modifier is composed of a second organic molybdenum compound and a liquid organic matter, wherein the second organic molybdenum compound is dialkyl dithiocarbamate molybdenum, and the liquid organic matter is obtained by mixing isooctyl oleate and triethanolamine borate in a volume ratio of 2 to 3:1; based on the total weight of the second modifier, the proportion of dialkyl dithiocarbamate molybdenum is 0.45 to 0.65wt%.

[0070] <Modified NdFeB magnetic powder and preparation method>

[0071] The present invention also provides a method for preparing modified NdFeB magnetic powder using the composite modifier as described above, comprising the following steps: 1) preparing rare earth alloy coarse powder; 2) preparing rare earth alloy fine powder; 3) preparing modified NdFeB magnetic powder. The method is described in detail below.

[0072] Preparation of rare earth alloy coarse powder

[0073] The raw materials including the rare earth alloy are smelted and crushed to obtain the rare earth alloy coarse powder.

[0074] In the present invention, the preparation of rare earth alloy coarse powder can refer to those known in the art. The smelting is carried out under vacuum conditions to obtain alloy strips, and the alloy strips can be subjected to hydrogen crushing to obtain rare earth alloy coarse powder. The particle size range of the rare earth alloy coarse powder can be 68 to 368 μm.

[0075] In the present invention, the raw materials comprising the rare earth alloy include rare earth elements (R), boron (B) and iron (Fe). Wherein, based on the total weight of the raw materials comprising the rare earth alloy, the R content is 29.0-33.0wt%, the B content is 0.88-0.95wt%, the Fe content is 62wt% or more, and the Fe content is preferably 64wt% or more. The raw materials comprising the rare earth alloy may also include elements such as copper (Cu), cobalt (Co), aluminum (Al), gallium (Ga), zirconium (Zr), and other inevitable impurities.

[0076] R may include light rare earth elements and heavy rare earth elements. In the present invention, the light rare earth elements may be lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm) and europium (Eu); the heavy rare earth elements may be gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu) and yttrium (Y).

[0077] According to one embodiment of the present invention, R does not contain heavy rare earth elements, R is selected from at least one of La, Ce, Nd, Pr, and Sm, and must contain Nd.

[0078] According to a specific embodiment of the present invention, the composition of the raw material including the rare earth alloy is as follows: PrNd 30.0-32.0wt%, Cu 0.12-0.18wt%, Co 0.3-0.7wt%, Al0.3-0.5wt%, Ga 0.15-0.25wt%, Zr 0.10-0.35wt%, B 0.88-0.92wt%, and Fe as the balance.

[0079] Preparation of rare earth alloy fine powder

[0080] Add the first modifier to the rare earth alloy coarse powder, and continue to refine and crush to obtain rare earth alloy fine powder; wherein the weight percentage of the first modifier to the rare earth alloy coarse powder is 0.2-0.95‰, preferably 0.3-0.7‰, more preferably 0.4-0.6‰, for example, 0.45‰, 0.5‰, 0.56‰. The first modifier in the composite modifier of the present invention is added to the rare earth alloy coarse powder, and the second modifier is not added first, which is more conducive to obtaining rare earth alloy fine powder with good fluidity and good oxidation resistance. In addition, the addition of the first modifier can shorten the airflow milling time and reduce the proportion of fine powder with a particle size of less than 1.5μm.

[0081] In the present invention, the further fine crushing can be performed by using a jet mill, and the jet mill can be any of those known in the art. 90 / D 10 The average specific surface area diameter is 3.7-4.46, the average specific surface area diameter is 2.45-2.68 μm, the repose angle is 43.5°-43.8°, and the bulk density is 1.72-1.76 g / cm 3 , tap density greater than or equal to 3.76g / cm 3 .

[0082] Preparation of Modified NdFeB Magnetic Powder

[0083] Add a second modifier to the rare earth alloy fine powder and mix them to obtain modified NdFeB magnetic powder, wherein the weight percentage of the second modifier to the rare earth alloy fine powder is 0.3-0.8‰, for example, 0.4‰, 0.5‰, 0.6‰, 0.76‰. The modified NdFeB magnetic powder obtained in this way is more conducive to one-time pressing and can still obtain a high-density compact when isostatic pressing is omitted. In addition, the magnetic properties of the obtained sintered NdFeB magnet can be significantly improved.

[0084] In the present invention, a shearing mixing method can be adopted during mixing, and specifically, a high-efficiency shearing mixer can be adopted for mixing.

[0085] <Sintered NdFeB magnet and preparation method>

[0086] The present invention also provides a method for preparing a sintered NdFeB magnet, comprising the following steps: pressing and sintering the modified NdFeB magnetic powder prepared as above to obtain a sintered NdFeB magnet, which is described in detail below.

[0087] In the present invention, the preparation of modified NdFeB magnetic powder is as described above and will not be described in detail here.

[0088] The modified NdFeB magnetic powder is oriented and pressed to obtain a compact with a higher density, and the isostatic pressing process can be omitted. This is because the specific modified NdFeB magnetic powder of the present invention, the present invention believes that the first organic molybdenum compound and the second organic molybdenum compound can provide stable adsorption and lubrication properties for the modified NdFeB magnetic powder, the magnetic powder has good fluidity, is easy to form the magnetic powder, is easy to orient, and is stable during orientation. Subsequently, when the modified NdFeB magnetic powder of the present invention is used to obtain a sintered NdFeB magnet, the present invention believes that the molybdenum element formed by the thermal decomposition of the first organic molybdenum compound and the second organic molybdenum compound can stabilize the grain boundary, reduce grain growth, and improve the grain boundary stability performance, thereby improving the magnetic properties of the resulting sintered NdFeB magnet.

[0089] In the present invention, the density of the green compact can be 4.0 to 4.5 g / cm3 According to a specific embodiment of the present invention, the green compact density is 4.10 g / cm 3 According to another specific embodiment of the present invention, the compact density is 4.15 g / cm 3 .

[0090] In the present invention, the sintering process includes:

[0091] Vacuum heat treatment: Place the pressed green body into a sintering furnace. -1 Pa, start heating to 180-460°C in the first temperature zone, and keep it in the first temperature zone for 30-120min, then heat it to 320-480°C in the second temperature zone, and keep it in the second temperature zone for 30-120min, then heat it to 1030-1105°C in the third temperature zone, and keep it at this temperature for 2-6h; the preferred temperature of the first temperature zone is 280-430°C, more preferably 310-390°C. The holding time in the first temperature zone is preferably 40-100min, more preferably 50-70min. The preferred temperature of the second temperature zone is 350-480°C, more preferably 400-460°C. The holding time in the second temperature zone is preferably 40-100min, more preferably 50-70min. The preferred temperature of the third temperature zone is 1050-1105°C, more preferably 1070-1100°C. The insulation time in the third temperature zone is preferably 3 to 5 hours, more preferably 3.5 to 4.5 hours.

[0092] Aging treatment: First stage aging, heating to 870-950℃, and keeping at this temperature for 0.5-5h; second stage aging, keeping at 400-665℃ for 1-5h; after aging treatment, cooling to room temperature. This is conducive to obtaining magnets with good magnetic properties and stability. In the sintered NdFeB magnet of the present invention, molybdenum is enriched in the grain boundaries and the edge areas of the main phase, and molybdenum mainly exists in the form of solid solution, high melting point compounds and complex intermetallic compounds, such as GaMox, FeMox, FeMoB, etc.

[0093] The preferred temperature for the first aging is 890-940°C, more preferably 895-920°C. The holding time for the first aging is preferably 1-4.5h, more preferably 2-4h. The preferred temperature for the second aging is 420-600°C, more preferably 470-550°C. The holding time for the second aging is preferably 1.5-4.5h, more preferably 2-3.5h.

[0094] In the present invention, the remanence of the obtained sintered NdFeB magnet is increased by 0.1 kGs or more, preferably by 0.35 kGs or more; the coercive force is increased by 1 kOe or more, preferably by 1.29 kOe or more; the maximum magnetic energy product is increased by 0.9 MGOe or more, preferably by 3.5 MGOe or more; the squareness is increased by 0.6% or more.

[0095] In the present invention, the oxygen content of the sintered NdFeB magnet is less than 535 ppm, and the carbon content is less than 700 ppm.

[0096] <Application>

[0097] The present invention also provides an application of the composite modifier as described above in improving the magnetic properties of sintered NdFeB magnets. The composite modifier of the present invention is formed by a first modifier and a second modifier. The first modifier and the second modifier are added at specific different stages to obtain a modified NdFeB magnetic powder containing the composite modifier. The magnetic properties of the sintered NdFeB magnet obtained by such modified NdFeB magnetic powder are significantly improved, and the carbon content, oxygen content, and nitrogen content are significantly reduced. The remanence of the obtained sintered NdFeB magnet is increased by more than or equal to 0.1 kGs, preferably more than or equal to 0.35 kGs; the coercive force is increased by more than or equal to 1 kOe, preferably more than or equal to 1.29 kOe; the maximum magnetic energy product is increased by more than or equal to 0.9 MGOe, preferably more than or equal to 3.5 MGOe; the squareness is increased by more than or equal to 0.6%. The oxygen content of the sintered NdFeB magnet is less than 535 ppm, and the carbon content is less than 700 ppm.

[0098] <Test Method>

[0099] Determination of magnetic properties: The magnetic properties of the sintered body and the sintered permanent magnet were measured at room temperature using a BH magnetometer to obtain the room temperature remanence, room temperature coercive force, and maximum magnetic energy product of the sintered body and the sintered permanent magnet.

[0100] Test of oxygen content and carbon content in sintered NdFeB magnets: The oxygen content is measured by ONH3500 analyzer, and the carbon content is measured by high-frequency infrared carbon-sulfur analyzer CS3500 analyzer. Both of the above equipment are produced by China Iron and Steel Research Institute Nano-Tech.

[0101] Example 1

[0102] Step 1: Prepare a rare earth alloy coarse powder according to the following components: PrNd 30.2wt%, Cu 0.14wt%, Co 0.35wt%, Al 0.4wt%, Ga 0.2wt%, Zr 0.15wt%, B 0.89wt%, Fe balance. The raw materials including the rare earth alloy are vacuum smelted to obtain rare earth alloy strip pieces, and the rare earth alloy strip pieces are hydrogen crushed to obtain a rare earth alloy coarse powder with a particle size range of 68 to 368μm.

[0103] Step 2: Add the first modifier to the rare earth alloy coarse powder, mix them initially, and then crush them by air jet mill to obtain rare earth alloy fine powder with fine particle size. The amount of the first modifier added is 0.50‰ of the weight of the rare earth alloy coarse powder. 90 / D 10 The average specific surface area diameter is 4.30, the average specific surface area diameter is 2.68 μm, the repose angle is 43.5°, and the bulk density is 1.72 g / cm 3 , tap density is 3.76g / cm 3 .

[0104] The preparation process of the first modifier is as follows: the first organic molybdenum compound in the first modifier is dialkyl dithiocarbamate molybdenum, with a molybdenum content of 26.8wt% and a sulfur content of 25.4wt%. 6.8g of dialkyl dithiocarbamate molybdenum is added to 85.6g of solid organic matter, stirred for 10min under nitrogen protection, and crushed to form a uniformly mixed powder. Then 1.2g of nano molybdenum disulfide is added to the uniformly mixed powder, and stirring is continued for 30min to obtain the first modifier containing the first organic molybdenum compound. The solid organic matter used above is a mixture of palmitic acid amide, erucic acid amide and ethylene bisoleamide, the weight proportion of palmitic acid amide and erucic acid amide is 82wt%, and the mass ratio of palmitic acid amide and erucic acid amide is 40:60.

[0105] Step 3: Add the second modifier to the rare earth alloy fine powder, and mix it for 30 minutes using a high-efficiency shear mixer to obtain modified NdFeB magnetic powder. The amount of the second modifier added is 0.4‰ of the weight of the rare earth alloy fine powder.

[0106] The preparation process of the second modifier is as follows: isooctyl oleate and triethanolamine borate are mixed in a volume ratio of 2:1, and then dialkyl dithiocarbamate molybdenum is added, and the weight proportion of dialkyl dithiocarbamate molybdenum is 0.45wt%.

[0107] Step 4: Orient and press the modified NdFeB magnetic powder to obtain a density of 4.10 g / cm 3 The green body is placed in a vacuum sintering furnace. When the vacuum degree is 10 -2Pa, start power sintering, first raise the temperature to 380℃, and keep it at 380℃ for 50min, then raise the temperature to 450℃, and keep it at 450℃ for 50min, then raise the temperature to 1085℃, and keep it at 1085℃ for 3.5h. The vacuum degree reaches 10 -3 ~10 -4 Pa, after the heat preservation at 1085℃, the blast cooling was performed to room temperature to obtain a sintered magnet; the sintered magnet was subjected to secondary aging treatment, specifically including: heating to the first aging temperature of 915℃, and heat preservation at this aging temperature for 3h; then heat preservation at the second aging temperature of 485℃ for 2h, and quickly cooled to room temperature after the heat preservation at 485℃ was completed to obtain a sintered NdFeB magnet. The performance test results of the obtained sintered NdFeB magnet are shown in Table 1.

[0108] Comparative Example 1

[0109] Compared with Example 1, in this comparative example, no molybdenum dialkyl dithiocarbamate is added to the first modifier, and the amount of molybdenum disulfide is 8.0 g; no molybdenum dialkyl dithiocarbamate is added to the second modifier, the addition amounts of the first modifier and the second modifier remain unchanged, and the remaining parameters and methods are the same as those in Example 1. The performance test results of the obtained sintered NdFeB magnet are shown in Table 1.

[0110] Comparative Example 2

[0111] Compared with Example 1, in this comparative example, no molybdenum dialkyl dithiocarbamate was added to the first modifier, and the amount of molybdenum disulfide was 8.0 g; the amount of the first modifier added remained unchanged, and the other parameters and methods were the same as those in Example 1. The performance test results of the obtained sintered NdFeB magnet are shown in Table 1.

[0112] Comparative Example 3

[0113] Compared with Example 1, in this comparative example, no molybdenum dialkyldithiocarbamate is added to the second modifier, the amount of the second modifier added remains unchanged, and the other parameters and methods are the same as those of Example 1. The performance test results of the obtained sintered NdFeB magnet are shown in Table 1.

[0114] Table 1

[0115]

[0116] As can be seen from Table 1, compared with Comparative Examples 1-3, the magnetic properties of the sintered NdFeB magnets prepared in Example 1 are significantly improved, and the carbon content and oxygen content are reduced. Compared with Comparative Example 1, the remanence of the sintered NdFeB magnets prepared by the present invention is increased by 0.14 kGs, the coercive force is increased by 1.48 kOe, the maximum magnetic energy product is increased by 1.19 MGOe, and the squareness is increased by 0.6%, which shows that the magnetic properties of the sintered NdFeB magnets prepared by the method of the present invention are significantly improved. The carbon content and oxygen content are both low.

[0117] Example 2

[0118] Step 1: Prepare a rare earth alloy coarse powder according to the following components: PrNd 30.2wt%, Cu 0.14wt%, Co 0.35wt%, Al 0.4wt%, Ga 0.2wt%, Zr 0.15wt%, B 0.89wt%, Fe balance. The raw materials including the rare earth alloy are vacuum smelted to obtain rare earth alloy strip pieces, and the rare earth alloy strip pieces are hydrogen crushed to obtain a rare earth alloy coarse powder with a particle size range of 68 to 368μm.

[0119] Step 2: Add the first modifier to the rare earth alloy coarse powder, mix them initially, and then crush them by air jet mill to obtain rare earth alloy fine powder with fine particle size. The amount of the first modifier added is 0.56‰ of the weight of the rare earth alloy coarse powder. 90 / D 10 The average specific surface area diameter is 4.34, the average specific surface area diameter is 2.45 μm, the repose angle is 43.8°, and the bulk density is 1.76 g / cm 3 , tap density is 3.80g / cm 3 .

[0120] The preparation process of the first modifier is as follows: the first organic molybdenum compound in the first modifier is oily molybdenum cyclopentane acid, with a molybdenum content of 5.8wt%. 5.2g of molybdenum cyclopentane acid is added to 158g of solid organic matter, heated under nitrogen protection (heating temperature is 180°C) and stirred for 30min, and crushed to form a uniformly mixed powder. Then 4.5g of nano tungsten disulfide is added to the uniformly mixed powder, and stirring is continued for 30min to obtain the first modifier containing the first organic molybdenum compound. The solid organic matter used above is a mixture of stearic acid amide, oleic acid amide and ethylenebiserucic acid amide, wherein the weight of stearic acid amide and oleic acid amide accounts for 80wt%, and the weight ratio of stearic acid amide and oleic acid amide is 20:80.

[0121] Step 3: Add the second modifier to the rare earth alloy fine powder, and mix it for 30 minutes using a high-efficiency shear mixer to obtain modified NdFeB magnetic powder. The amount of the second modifier added is 0.6‰ of the weight of the rare earth alloy fine powder.

[0122] The preparation process of the second modifier is as follows: oleic acid isooctyl ester and triethyl borate are mixed in a volume ratio of 4:3, and then alkyl salicylic acid molybdenum (the alkyl group in the alkyl salicylic acid molybdenum is a straight chain of C12 to C18) is added, and the weight of the alkyl salicylic acid molybdenum accounts for 1.58wt%.

[0123] Step 4: Orient and press the modified NdFeB magnetic powder to obtain a density of 4.15g / cm 3 The green body is placed in a vacuum sintering furnace. When the vacuum degree is 10 -2 Pa, the sintering was started, the temperature was first raised to 390℃, and kept at 390℃ for 50min, then raised to 470℃, and kept at 470℃ for 50min, then raised to 1075℃, and kept at 1075℃ for 3.5h, and the vacuum degree reached 10 -3 Pa~10 -4 Pa, after the insulation at 1075℃, the sintered magnet is cooled to room temperature by blasting; the sintered magnet is subjected to secondary aging treatment, specifically including: heating to the first aging temperature of 913℃, and insulation at this aging temperature for 2.6h; then insulation at the second aging temperature of 485℃ for 2h, and rapid cooling to room temperature after the insulation at 485℃ is completed, to obtain a sintered NdFeB magnet. The performance test results of the obtained sintered NdFeB magnet are shown in Table 2.

[0124] Comparative Example 4

[0125] Compared with Example 2, in this comparative example, no molybdenum cyclopentaneate is added to the first modifier, the amount of tungsten disulfide is 9.7 g, and the weight of the first modifier is 225 g; no alkyl salicylate molybdenum is added to the second modifier, the addition amounts of the first modifier and the second modifier remain unchanged, and the other parameters and methods are the same as in Example 2.

[0126] Table 2

[0127]

[0128] As shown in Table 2, compared with Comparative Example 4, the remanence of the sintered NdFeB magnet prepared by the present invention is increased by 0.37 kGs, the coercive force is increased by 1.29 kOe, the maximum magnetic energy product is increased by 3.97 MGOe, and the squareness is increased by 0.6%, which shows that the magnetic properties of the sintered NdFeB magnet prepared by the method of the present invention are significantly improved. The carbon content and oxygen content are both low.

[0129] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A composite modifier for NdFeB magnetic powder, characterized in that: It is formed by a first modifier and a second modifier, Wherein, the first modifier comprises a first organic molybdenum compound, a solid organic substance and a solid inorganic substance; the second modifier comprises a second organic molybdenum compound and a liquid organic substance; Wherein, the solid organic matter is selected from at least one of higher alcohols, higher carboxylic acids, higher fatty acid esters and amide compounds; the solid inorganic matter is a two-dimensional layered substance selected from at least one of molybdenum disulfide, tungsten disulfide and vanadium selenide; the liquid organic matter includes fatty acid esters and organic boron compounds; wherein the first organic molybdenum compound is the same as or different from the second organic molybdenum compound; Wherein, based on the total weight of the first modifier, the weight percentage of the first organic molybdenum compound is 0.3-15wt%, and the weight percentage of the solid inorganic substance is 0.02-4.8wt%; Wherein, based on the total weight of the second modifier, the weight percentage of the second organic molybdenum compound is 0.2 to 18 wt %; Wherein, the weight ratio of the first modifier to the second modifier is 0.4-0.95:0.3-0.

8.

2. The composite modifier according to claim 1, characterized in that The first organic molybdenum compound or the second organic molybdenum compound is selected from one or more of a molybdenum amine complex, molybdenum cyclopentaneate, nitrogen-containing dialkyl dithiophosphoryl molybdenum, dialkyl dithiocarbamate molybdenum, dialkyl dithiophosphoryl molybdenum, alkyl salicylate molybdenum and isooctanoic acid molybdenum.

3. The composite modifier according to claim 1, characterized in that The higher alcohol is selected from at least one of tetradecanol, hexadecanol, stearyl alcohol and eicosanol; the higher carboxylic acid is selected from at least one of lauric acid, myristic acid, palmitic acid and stearic acid; the higher fatty acid ester is selected from at least one of lauric acid monoglyceride, myristic acid glyceride and palmitic acid glyceride; the amide compound is selected from at least one of oleamide, ethylene bisoleamide, palmitic acid amide, oleyl palmitic acid amide, stearic acid amide, ethylene biserucic acid amide and erucic acid amide; The fatty acid ester is selected from at least one of isooctyl oleate, methyl oleate, methyl palmitate, methyl stearate and methyl laurate; the organic boron compound is selected from at least one of triethanolamine borate, triisopropyl borate, tributyl borate and triethyl borate.

4. A method for preparing modified NdFeB magnetic powder using the composite modifier according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) smelting and crushing raw materials including rare earth alloy to obtain rare earth alloy coarse powder; 2) adding a first modifier to the rare earth alloy coarse powder, and continuing to refine and crush to obtain rare earth alloy fine powder; wherein the weight percentage of the first modifier to the rare earth alloy coarse powder is 0.4-0.95‰; 3) adding a second modifier to the rare earth alloy fine powder and mixing them to obtain modified NdFeB magnetic powder, wherein the weight percentage of the second modifier to the rare earth alloy fine powder is 0.3-0.8‰.

5. The method according to claim 4, characterized in that: The particle size of the rare earth alloy coarse powder ranges from 68 to 368 μm; The rare earth alloy fine powder has a D 90 / D 10 The average specific surface area diameter is 3.7-4.46, the average specific surface area diameter is 2.45-2.68 μm, the repose angle is 43.5°-43.8°, and the bulk density is 1.72-1.76 g / cm 3 , tap density greater than or equal to 3.76g / cm 3 .

6. A modified NdFeB magnetic powder, characterized in that: It is prepared according to the method according to claim 4 or 5.

7. A method for preparing a sintered NdFeB magnet, characterized in that: The preparation method comprises the following steps: The modified NdFeB magnetic powder as claimed in claim 5 is pressed and sintered to obtain a sintered NdFeB magnet.

8. The preparation method according to claim 7, characterized in that: The sintering process comprises: Vacuum heat treatment: Place the pressed green body into a sintering furnace. -1 Pa, start heating to the first temperature zone of 180-460°C, and keep it in the first temperature zone for 30-120 minutes, then heat up to the second temperature zone of 320-480°C, and keep it in the second temperature zone for 30-120 minutes, then heat up to the third temperature zone of 1030-1105°C, and keep it at this temperature for 2-6 hours; Aging treatment: For the first stage of aging, the temperature is raised to 870-950℃ and kept at this temperature for 0.5-5h; for the second stage of aging, the temperature is kept at 400-665℃ for 1-5h; after the aging treatment, it is cooled to room temperature.

9. A sintered NdFeB magnet, characterized in that: It is prepared according to the preparation method according to claim 7.

10. Use of the composite modifier according to claim 1 in improving the magnetic properties of sintered NdFeB magnets, characterized in that: The remanence of the sintered NdFeB magnet is increased by 0.1 kGs or more, the coercive force is increased by 1 kOe or more, the maximum magnetic energy product is increased by 0.9 MGOe or more, and the squareness is increased by 0.6% or more.

Citation Information

Patent Citations

  • Molybdenum nano powder composite neodymium iron boron magnet and preparation method thereof

    CN115896643A

  • Process for preparing high-performance neodymium-iron-boron magnet by hot pressing method

    CN117936258A